Literature Study On Competitive Advantage In Official Schools Which Is Influenced By Factors: Competitive Strategies, Leadership, And Competence - Feti Fatonah Fatonah (Dinasti Publisher, 2023)
Competitive advantages are the formulation strategies of organizations or educational institutions designed to achieve opportunities that cannot be imitated by competitors to maximize profits. Competitive advantage is the key to success for organizations or companies that are in an environment that is constantly experiencing rapid changes in a fiercely competitive environment and in an increasingly short period of time. so it is important for an organization to understand the phenomenon of the relationship and influence between competitive advantage and the factors of competitive strategy, leadership, and competence, This article is a literature review of the factors1 that affect competitive advantage in official school educational institutions, namely competitive strategy, leadership, and competence. This literature study aims to hypothesize the influence of these three factors on the competitive advantage of organizations. The results of this literature review show that all study variables: competitive strategy, leadership, and competence, have a significant effect on competitive advantage. This study is expected to help further research efforts to increase competitive advantage in educational institutions. Keywords: Competitive advantage, competitive strategy, leadership, and competence.